NUTRITIONAL COMPOSITION AND BIOACTIVE PROPERTIES OF THE WHOLEGRAIN FLOUR OBTAINED FROM MAIZE INBRED LINES - Nikolić, Valentina (Food and Feed Research, 2023)
The objective of this study was to assess the chemical composition and bioactive properties of the wholegrain flour obtained from eleven maize inbred lines in order to identify genotypes with increased potential for the development of hybrids with high nutritional and functional value, suitable for food production. The maize inbreds, including seven standard yellow, two QPM and two red kernel lines, were grown in the experimental field of the Maize Research Institute at the location of Zemun Polje, Serbia. Wholegrain maize flour was obtained by grinding the maize grain on a laboratory mill. The assessment of the chemical composition and content of certain bioactive compounds, as well as total antioxidant capacity, was conducted using standard laboratory procedures. The highest starch content (73.73%), was determined in line L8, while line L10 had the highest protein content (12.82%). Among soluble proteins, the α-zein fraction was dominant in most of the lines, ranging from 0.92% to 3.57%. The highest content of total fibers (NDF) was determined in red kernel line L9 (15.77%). Line L8 was the richest in total carotenoids (21.08 μg βCE/g d.m.), while line L7 had the highest total antioxidant capacity (34.30 mmol Trolox/kg d.m.), which can be explained by the presence of anthocyanins in the red grain. Line L1 had the highest content of total sugars (3.36%), and line L4 had the lowest (1.44%). All samples of inbred lines investigated in this study showed good quality parameters regarding chemical composition and bioactive properties. The obtained results may provide some valuable guidelines needed in the following stages of maize breeding as well as open up various possibilities for the utilization of wholegrain maize flour in the food industry.
Keywords: maize, wholegrain flour, inbred lines, nutritional composition, bioactive properties